UCLA Loneliness Scale in Nepal - Bhusal, Durga; Adhikari, Keshab Prasad; Chalise, Hom Nath (Butwal Campus Journal, 2023)
The intention of this examination was to present innovative empirical evidence regarding the adaptation of the UCLA Loneliness Scale to Nepal and investigate the validity and reliability of the scale for Nepalese young elderly. The participants in this study were 513 young senior citizens aged in the age range 60 and 74. Among the participants, 243 (47.4%) were male, 270 (52.6%) were female and the mean age was found to be 65.86 (SD = 4.203). Principal Component Analysis (PCA) and Maximum Likelihood Analysis were used to evaluate the UCLA loneliness scale. The factor analysis resulted in one factor, where factor loadings of the items varied between 0.561 and 0.784 measuring in SPSS 20. The LISREL 8.8 program showed the factor loadings through ordinal analysis in the range of 0.695 and 0.917, and accordingly calculated Average Variance Explained (AVE) was 0.72. The computation of Cronbach alpha level was 0.945 and composite reliability was 0.98 in the examination of internal consistency of the variables. Findings suggested that the UCLA loneliness scale was found appropriate for use among Nepalese young senior citizens.